POTENSI ARANG AKTIF TULANG SAPI SEBAGAI ADSORBEN ION TIMBAL, KADMIUM, NITRAT DAN KLORIDA DALAM LARUTAN - Ayu Antika; Sofia Anita; Tengku Abu Hanifah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Cow bone can be used as raw material of craft. Based on the development of science and technology cow bone can be utilized for many purposes, for example, it could be as an adsorbent. Cow bone can also be used as an activated charcoal, because bone contains about 35% of organic compounds. Activated charcoal was made of cow bone through carbonization and activation processes. The activation process used Na 2 CO 3 as an activator which the concentration is 2,5%, 5% and 7,5%. In this experiment, activated carbon of cow bone was used to adsorbed is cadmium, lead, nitrate and chloride ions in solution. Cadmium and lead were analyzed using atomic absorption spectrophotometer (AAS), while chloride was analyzed using Argentometry Mohr method and nitrate was analyzed using Brusin Sulfate method. The adsorption capacity of the activated charcoal cow bones to cadmium, lead, nitrate and chloride ions are 99.9643%, 99.9481%, 90.5885% and 10.145% respectively.